(untitled) (Proceedings of International Educators Conference, 2022)
The author of this article analyzes the necessity of using artificial intelligence in various sphere of our life. In addition, the author reviewed the conception of artificial intelligence. Besides, it has been put forward the proposals on development of legal framework of artificial intelligence as well as adopting Act on artificial intelligence, Strategy of development of artificial intelligence and code of ethics of artificial intelligence.